Enterprise Risk Management (ERM): an empirical analysis of factor associated with PLC firm value in Malaysia - Chong, Ming Er; Lee, Sueh Wen; Saw, Teong Yew; Toh, Siew Zen; Yip, Yen Sim (2019)
The aim of this research was to investigate the impact of selected explanatory variables on firm value of Malaysian Public Listed Companies over the study period in year 2017. The selected explanatory variables are Enterprise Risk Management (ERM), firm size, debt-to-equity, return on assets, dividend per share (DPS) and earning per share (EPS). Ordinary Least Square (OLS) method was implemented to the research to examine the significant relationship among the firm value and explanatory variables by using 500 listed firms from Bursa Malaysia. The empirical results concluded that debt-to-equity, and return on assets, had statistically significant positive effect on firm value. However, firm size had found out a significant negative impact on firm value. Finally, ERM, DPS, and EPS had statistically insignificant positive effect on firm value.